Skills education: prospects and challenges for the education system - Portillo Torres, Mauricio Cristhian (2017)
This paper analyzes the Project DeSeCo - Programme for International Student Assessment (PISA), Assessment and Teaching of 21st Century Skills (ATC21S) and Life Skill Based Education (WHO).  There is an ongoing process to change the current curriculum to a skill-based curriculum and an analysis of the theoretical foundations of these three projects are mentioned. Based on these assumptions there are identified five challenges for the educational system: the construction of solid progress maps for skills, more formative than summative assessment, trajectory of learning based on mastery and not in marks, time variable in diversity, and differentiated support based on individual learning needs. Also, there are some issues that must be considered in order to implement this curriculum change.